Comparison of radiological and clinical outcomes of 3D-printed artificial vertebral body with Titanium mesh cage in single-level anterior cervical corpectomy and fusion: A meta-analysis - Cheng, Haiyang; Luo, Gan; Xu, Dan; Li, Yuqiao; Wang, Ziqi; Yang, Houzhi; Liu, Yang; Jia, Yutao; Sun, Tianwei (Frontiers in Surgery, 2023)
Propose This meta-analysis aimed to determine whether 3D-printed artificial vertebral body have superior clinical and radiographic outcome than Titanium Mesh Cage(TMC) in single-level anterior cervical corpectomy and fusion. Methods A comprehensive search of the PubMed, Embase, Cochrane Library, Web of Science, and CNKI (China National Knowledge Infrastructure) databases was conducted to find randomized control trials (RCTs) or cohort studies that compared 3D-printed artificial vertebral body with conventional Titanium Mesh Cage (TMC) in single-level anterior cervical corpectomy and fusion (SL-ACCF). Operation time; intraoperative blood loss; subsidence of vertebral body; preoperative, and final follow-up C2–C7 Cobb angle, Japanese Orthopedic Association (JOA) scores, and Visual Analog Scale(VAS) scores were collected from eligible studies for meta-analysis. Results We included 6 cohort studies with 341 patients. The results of the meta-analysis showed that the 3D group has a shorter operation time than the traditional TMC group(p = 0.04) and the TMC group had more severe subsidence(≥3 mm) of vertebral body than the 3D group(p < 0.0001). And the cervical C2–C7 Cobb angle in the 3D group was larger than that in the TMC group at the final follow-up. Conclusion This meta-analysis demonstrates that 3D-printed artificial vertebral body is superior to traditional TMC in reducing the operation time and maintaining the postoperative vertebral height and restoring sagittal balance to the cervical spine in single-level anterior cervical corpectomy and fusion.